PEMBERDAYAAN TENAGA ADMINISTRASI SEKOLAH DALAM MENINGKATKAN KINERJA PELAKSANAAN TUPOKSI - Ahmad Salim; Endi Rochaendi (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
This study aims to describe the process of empowering school administrative personnel which includes awareness, capacity building and empowerment. This study uses a qualitative approach with data collection techniques through interviews, observation and study of the documentation. The data analysis model used an interactive analysis model from Miles Huberman. The results show that the empowerment of school administrative personnel which included awareness, capacity and empowerment stages have been implemented quite successfully so that school administrative staff had various competencies (personality, social, technical and managerial). In the awareness stage, it is carried out to provide encouragement, motivation and communication to school administration staff to increase their adaptability to their main tasks and functions. At the capacitating stage, education and training are carried out in the form of upgrading, education and training, technical guidance and workshops. Meanwhile, at the empowerment stage, apperception and self-potential development activities are carried out. In this empowerment, there is also support from school leaders with full dedication and motivation to empower school administrative personnel. However, there is still a need for reasonably fundamental improvements in empowerment with respect to various constraints and conditions that are expected in the next empowerment process. For this purpose, it is necessary to review (remodify) empowerment programs, so that they are validative, varied, dynamic, evaluative, interesting and weighty, including the consideration of the needs of school administrative personnel.